A concept paper on readiness in artificial intelligence (AI) mastery and its impact on 21st century pedagogy among pre-service history teachers - Arzizul Bin Antin; Dg Norizah binti Ag Kiflee Dzulkifli (RSIS International, 2025)
This concept paper investigates the readiness of pre-service History teachers to integrate Artificial Intelligence (AI) into secondary school education, in response to the increasing influence of advanced technologies in contemporary pedagogy. Anchored in Vygotsky’s Constructivist Theory and the Technological Pedagogical Content Knowledge (TPACK) framework, the study aims to explore the gap between teachers’ awareness of AI and their practical and ethical preparedness to implement AI tools in the 21st century pedagogy classroom. Employing a mixed-methods design, the proposed study will gather quantitative data through structured questionnaires administered to 100 teacher trainees and qualitative insights via in-depth interviews with 20 selected participants. Preliminary observations suggest that while awareness of AI is relatively high among pre-service teachers, there is limited understanding of its pedagogical applications and ethical implications. Key barriers include insufficient training, limited access to digital infrastructure, and lack of institutional support, alongside concerns about data privacy and algorithmic bias. Despite these limitations, pre-service teachers express a strong interest in the potential of AI to enhance differentiated instruction, automate administrative tasks, and improve student engagement. This paper advocates for comprehensive reform in teacher education, emphasizing the integration of experiential AI training, faculty upskilling, equitable technological access, and digital ethics instruction. By addressing these areas, teacher preparation programs can cultivate educators who are not only technologically adept but also ethically informed and pedagogically innovative. The findings from this proposed study aim to contribute to ongoing discourse on equipping future teachers to navigate and lead in AI-augmented educational environments.